Adaptive Lighting for Computer Vision - Cabrera, Mario (My University, 1983)
A system capable of adjusting a computer vision system to unpredictable ambient lighting has been designed and attached to a silhouette robot vision system. Its principle of operation is based on the generation and analysis of the distribution of light in one T.V. frame. Designed to be used in robot vision applications, high speed processing of data is achieved in the system to generate a histogram of grey levels in one frame time. An addressable RAM technique for this purpose is explained. The system obtains two threshold values from the histogram of grey levels and places them into a threshold logic unit. A silhouette from a grey level picture is obtained as the result of the process. Adaptability of the system is performed by using different integration times in the read out of the visual transducer. The implementation of the system is based on a video rate histogram generator, a sensitivity control unit, a DMA circuit, an 86/12A microcomputer and a solid state T.V. camera. A graphics printer is used to print out results and a CRT terminal to communicate with the microcomputer. The custom hardware and software implementations for the system are depicted in detail.
Keywords: adaptive lighting; computer vision